Prevailing against the odds of dropping out of school in Ghana - Sottie, C. A.; Awasu, C. (African Journal of Education and Technology, 2011)
This paper examines factors that affect school dropout at the basic level of education in Ghana. The study focuses on the experiences of students, parents, teachers and welfare workers. Weak family support, poor academic performance, poor school quality and low value for education are identified as important to children’s stay in school. It is observed that some children prevail against the odds and remain in school while others drop out. Resilience is identified as an important factor that could enhance the capacity of at-risk student to stay in school despite adverse circumstances. The study recommends research on the underlying processes that foster personal resilience in school age children from disadvantaged backgrounds in Ghana